SURVEY ON THE EXISTENCE OF THE INFORMAL SECTOR DURING THE COVID-19 PANDEMIC (Case Study In Mataram City, West Nusa Tenggara Province) - Suprianto Suprianto; Eka Agustiani; Mohammad Alwi (UNIVERSITAS PAKUAN, 2021)
The purpose of this research is to The purpose of the study was to analyze the income and welfare level of informal sector workers during the Covid-19 pandemic in the city of Mataram. The research method was carried out by means of a survey by taking a sample of 60 respondents, and as many respondents as possible were determined by chance by looking at the characteristics of the informal sector workers. The data collected will be analyzed quantitatively and qualitatively. Qualitative analysis is used to explain or explain data from field research as a support for quantitative analysis. The characteristics of informal and formal workers mostly sell in crowded places with dense population and visitors in the area of Mataram city seen from the level of education 56.7% have education equivalent to high school and above and 43.3% have graduated from junior high and elementary school with an average the average length of work is more than 10 hours a day, while the average family dependents for informal and formal workers are between 2 and 4 dependents. The average income earned by informal workers is below Rp 2,000,000, - as many as 25 respondents, 41.67% and income above Rp 2,000,000, - for 20 respondents or 33.33%. While the income of informal workers on average is above IDR 3,000,000, as many as 11 respondents, 18.33%, the rest of the income above IDR 5,000,000, as many as 4 respondents or 6.67% is obtained by fried rice traders and food stalls.total income analysis of informal workers if according to the Sajogyo criteria level with an equivalent size, then the poor category is 68.33% with an expenditure / capita / year of 450 kg - 650 kg equivalent to the value of rice / year. While the remaining 31.67% or as many as 19 respondents are at the threshold of affluent living with per capita expenditures / year above 750 kg as many as 9 respondents. While the decent living category if the competition per capita / year is higher than 960 kg equivalent to the value of rice / year as many as 10 respondents or 16.67%. Overall, the income received by informal workers during the Covid-19 pandemic decreased by 40% compared to before the Covid-19 pandemic. To further increase the income of informal workers, in particular, to increase the working time of at least 15 hours per day and to open sales services through social media (medsos) with a digital system via the internet with Go food and Go-jek services, especially for traders of cooked food such as restaurants, fresh vegetables, rice and beverage traders.